Sira Dia Pangasinan vertical fishery - Fronda, Hannah Lei B.; Silvestre, Jose Danilo (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
The proposed facility seeks to address the incompatibility of the existing aquaculture facilities with the changing environment that breeds unoptimized fish productions, water pollution and overall economic decline through an updated fishery facility combining modern fishing technologies with traditional fish farming. After conducting an analysis of the fish kill problem and the current and thriving fishing technologies, the proponent geared towards designing an elevated fishery facility for the fishermen and the city government that will provide more stable yields and less dependence in the environment, through the use of the aquaponics system, a combination of aquaculture and hydroponics. To support the facility's aim to function as a transition space and a production facility for the people of Dagupan City, the concept of integration between aquaculture and aquaponics is translated through the building circulation and water management. Looking forward to the future, the facility is also quipped with sustainable materials and principles of harnessing rainwater.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Aquaculture facilities -- Design